Infinite series and generalized Integrals : (Detailed lessons supported by various exercises) - Guedda, Lamine (University of Eloued جامعة الوادي, 2024)
This manuscript includes a collection of lessons that fully cover the prescribed program for Analysis 03 Module and it is aimed primarily at second year undergraduate mathematics students. It is divided into 4 parts linked in their entirety to numerical series, sequences and series of functions, such as integer series and Fourier series, as well as to the generalized integral and to the various convergence tests. The lessons are supported by various solved and unsolved examples and exercises. الملخص: تتضمن هذه المطبوعة مجموعة من الدروس تغطي بالكامل المنهج المقرر لمقياس التحليل 03 وتستهدف في المقام الأول طلاب السنة الثانية ليسانس رياضيات. وهي مقسمة إلى 4 أجزاء تتعلق في مجملها بالسلاسل العددية والمتتاليات وسلاسل الدوال، مثل سلاسل القوى سلاسل فورييه، بالإضافة إلى التكامل المعمم ومعايير التقارب المختلفة. الدروس مدعمة بالعديد من الأمثلة والتمارين المحلولة وغير المحلولة.
Pedagogical Sopports
Keywords: Numerical series, partial sums, series of functions, sequence of functions, Fourier series, Power series, generalized integral, simple convergence, normal and uniform convergence; سلسلة عددية ،مجاميع جزئية ، متتالية توابع، سلسلة توابع، سلسلة فوريية، سلسلة صحيحة، تكامل معمم، التقارب البسيط، التقارب النظيمي والمنتظم.